Feeding Patterns, Mother-Child Dietary Diversity and Prevalence of Malnutrition Among Under-Five Children in Lebanon: A Cross-Sectional Study Based on Retrospective Recall - Abi Khalil, Huguette; Hawi, Mariam; Hoteit, Maha (Frontiers in Nutrition, 2022)
Despite demonstrated benefits, most countries fall short of meeting international targets for breastfeeding patterns, optimal complementary feeding, mother-children’s quality diet and malnutrition among under 5 children. The purpose of this study is to retrospectively 1) examine the under-five children’s (0-59 months) feeding habits, 2) investigate the mother-child’s dietary diversity, and 3) the prevalence of wasting, stunting, underweight and overweight in the under-five offspring living in households located in the main two provinces in Lebanon (Beirut and Mount Lebanon) was determined. The data for this analysis were collected from a representative sample of 384 households (384 mothers (21-49 years old) and children (0-59 months)) between February 2019 and June 2019. A questionnaire was used to inquire mothers of children aging 0-23 months about exclusive breastfeeding, continuous breastfeeding, exclusive bottle feeding, mixed feeding and complementary feeding patterns. Moreover, additional questions regarding dietary diversity were asked to mothers of children aged 6 to 59 months. Moreover, stunting, wasting, overweight and underweight were calculated using the z-score for height-for-age (HAZ), weight-for-height (WHZ) and weight-for-age (WAZ), respectively. Around 9.3% of children aged under 5 years were underweight (WAZ<-2SD to -3SD), 6.5% were at risk of being overweight, 24.45% were overweight, 9.3% were stunted (HAZ<-2 SD to-3SD) and 6.25% (WHZ<-2 SD to-3SD) were wasted. In total, the prevalence of EBF at 40 days and 6 months was 27%, and 30%, respectively. The prevalence of CBF was 23%. Around 60% of mothers breastfed their offspring between 0 and 6 month and half of them introduced infant formula at earlier stages between 0-6 months. As for dietary diversity (DD), one out of two mothers and one out of three children (6-59 months) had a low DD score (DDS) (46% and 32%, respectively). Regression analysis showed that children’s DD increases around 2 times (AOR=1.7; 95% CI (1.042 - 2.914)) in context of high maternal DDS, and about 12 times (AOR=11.7; 95% CI (1.2 – 111)) when being member of highest-income households . Our findings demonstrated low rates of EBF and CBF, high prevalence of EBOT and early introduction of complementary foods among children aged 0-59 months.